The Design of a Cash Concentration System - Stone, Bernell K.; Hill, Ned C. (Journal of Financial and Quantitative Analysis, 1981)
Cash concentration is the task of moving funds from depository banks into the central cash pool. It is useful to structure cash concentration by dividing it into two major problems––management and design. Management is the day-to-day operation of the cash concentration system once it is designed. Design is specifying the structure of the cash concentration system.